Healing and prevention of relapse of reflux oesophagitis by cisapride. Issue 11 (November 1991) - Toussaint, J; Gossuin, A; Deruyttere, M; Hublé, F; Devis, G
Abstract : Altogether, 138 patients were included in a study aimed at evaluating the effect of cisapride on healing and relapse of oesophagitis shown endoscopically. In the first phase of the study cisapride was given in an open fashion at 10 mg four times a day for 8 to 16 weeks, and healing was obtained in 69% of patients. Healing occurred later in patients with grades II to IV oesophagitis. The total score for reflux symptoms decreased by 67%. Eighty of the healed patients were included in the second phase. They were randomly assigned to double blind treatment with either cisapride 10 mg (n = 37) or placebo (n = 43) twice a day. Control endoscopy was performed when symptoms recurred or at the end of the six month trial. The cumulative percentage of patients in remission was higher (p = 0.06, survival analysis) in the cisapride group than in the placebo group, the relapse rates being 20% and 39%. The duration of remission tended to be longer in patients with a lower initial degree of oesophagitis. Adverse effects were no more frequent with cisapride than with placebo. In conclusion, cisapride is efficacious in healing oesophagitis, and, unlike other gastrointestinal prokinetic drugs or low dose cimetidine (400-800 mg daily) or ranitidine (150 mg daily), it may prevent relapse of oesophagitis.